(untitled) (Research, Society and Development, 2020)
The present study aimed to investigate the knowledge of women treated at a Health Center in the interior of Paraíba about risk and protective factors for breast cancer. It was a field, cross-sectional and qualitative research. A sociodemographic questionnaire and a semi-structured interview were applied. The Theoretical Saturation technique was used for the sample composition, which resulted in the participation of 20 women attended at a health center in Paraíba. The treatment of the data was carried out based on the Bardin Content Analysis. The average age was 39.1 (± 14.02) years. Most of the women interviewed was married (25%), attended high school (40%), lived in Campina Grande (75%), was Christians (90%) and 75% did not report breast cancer in the family. The categories that emerged from the speeches were: genetics and heredity; hormone replacement; traumas; conducting preventive exams or not; media and lectures. Regarding the source of information, the media stood out the most, especially television, in addition to the lectures. Although some conditions possibly favor access to health services, it is clear that the knowledge about risk and protective factors for the disease is quite limited, pointing out the need for further clarification by the population.